2021
DOI: 10.11124/jbies-20-00114
|View full text |Cite
|
Sign up to set email alerts
|

Health technologies for the prevention and detection of falls in adult hospital inpatients: a scoping review

Abstract: Objective: The objective of this scoping review was to examine and map the evidence relating to the reporting and evaluation of technologies for the prevention and detection of falls in adult hospital inpatients.Introduction: Falls are a common cause of accidental injury, leading to a significant safety issue in hospitals globally, and resulting in substantial human and economic costs. Previous research has focused on community settings with less emphasis on hospital settings to date. Inclusion criteria: Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…from the results to be fully explored and identified. 32 A similar approach was also taken in a recent scoping review on medical education, where, once the researchers had gathered preliminary findings, knowledge users were asked to check whether the findings resonated with their experience. The authors then asked the knowledge users to suggest topics for discussion and future research.…”
Section: Exemplar Projectsmentioning
confidence: 99%
See 2 more Smart Citations
“…from the results to be fully explored and identified. 32 A similar approach was also taken in a recent scoping review on medical education, where, once the researchers had gathered preliminary findings, knowledge users were asked to check whether the findings resonated with their experience. The authors then asked the knowledge users to suggest topics for discussion and future research.…”
Section: Exemplar Projectsmentioning
confidence: 99%
“…A recent scoping review on fall prevention and detection technologies for adult hospital in-patients involved a mixed review team including evidence synthesis methodologists, an information specialist, service users, a geriatrician, as well as a Falls Lead, Patient Safety Manager and Lead Moving and Handling Facilitator from a local health board 32 . The contribution from all partners enabled the “so what?” questions (what do the results tell us and what should we do now?)…”
Section: Exemplar Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy for this review was part of a larger scoping review investigating general approaches to adult falls prevention and detection in hospital settings [9]. The search strategy was developed in consultation with a research librarian, with the aim of identifying published and unpublished literature.…”
Section: Search Strategymentioning
confidence: 99%
“…During full-text screening for the larger scoping review [9], relevant studies were identified as being suitable for inclusion in this effectiveness review.…”
Section: Study Screening and Selectionmentioning
confidence: 99%